2020
DOI: 10.1021/acschemneuro.0c00482
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 Inhibitor Alleviates Autism-like Phenotype in a Prenatal Valproic Acid-Induced Mouse Model

Abstract: Autism spectrum disorder (ASD) is a severe neurological and developmental disorder that impairs a person's ability to socialize and communicate and affects behavior. The number of patients diagnosed with ASD has risen rapidly. However, the pathophysiology of ASD is poorly understood, and drugs for ASD treatment are strikingly limited. This study aims to evaluate the roles of glyoxalase 1 (GLO1)−methylglyoxal (MG)−γ-aminobutyric acid (GABA) signaling in ASD using a valproic acid (VPA)-induced animal model of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Overexpression of Glo1 in mice on a transgenic bacterial artificial chromosome [ 36 ] and overexpression of Glo1 only in neurons displayed enhanced anxiety-like behavior [ 37 ]. Consistent with these findings, treatment with a GLO1 inhibitor reduced anxiety-like behavior [ 36 , [38] , [39] , [40] ], as summarized in Table 2 . Glo1 knockout (KO) mice have also been reported to exhibit less anxiety-like behavior [ 41 ].…”
Section: Animal Modelssupporting
confidence: 66%
See 1 more Smart Citation
“…Overexpression of Glo1 in mice on a transgenic bacterial artificial chromosome [ 36 ] and overexpression of Glo1 only in neurons displayed enhanced anxiety-like behavior [ 37 ]. Consistent with these findings, treatment with a GLO1 inhibitor reduced anxiety-like behavior [ 36 , [38] , [39] , [40] ], as summarized in Table 2 . Glo1 knockout (KO) mice have also been reported to exhibit less anxiety-like behavior [ 41 ].…”
Section: Animal Modelssupporting
confidence: 66%
“…A recent study on prenatal treatment with valproic acid (VPA) in a mouse model of autism showed enhanced GLO1 expression and reduced MG levels in the brain [ 38 ]. Furthermore, GLO1 inhibitors ameliorated the autism-like phenotype in VPA-treated mice through GABA A stimulation by MG.…”
Section: Animal Modelsmentioning
confidence: 99%
“…It is important to note that a recent publication studied the effect of prenatal exposure to valproic acid (VPA) on Glo1 levels in postnatal mice. Here, the researchers found that VPA exposure during gestation results in increased Glo1 levels starting at 8 weeks postnatally which are accompanied by ASD-like behaviors [26]. It is interesting to observe that two different environmental factors can cause different outcomes of Glo1 expression, in relation to ASD progression.…”
Section: Discussionmentioning
confidence: 85%
“…In 80s of the XX century, autism was considered a relatively rare disease. In recent decades, however, the percentage of ASD diagnosing is growing steadily [ 5 9 ]. According to the current epidemiological studies, the rate of revealing these disorders is in the range of 0.5–1% per 150 individuals allowing them to be considered as widespread neurological diseases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%